2007
DOI: 10.1038/sj.mp.4001985
|View full text |Cite|
|
Sign up to set email alerts
|

New genes associated with schizophrenia in neurite formation: a review of cell culture experiments

Abstract: New genes consistently associated with schizophrenia include NRG1, Akt, DISC-1 and dysbindin-1. Since these genes participate in neurotransmission, neuroplasticity and neurodevelopment it has not been easy to elucidate which of these roles are abnormal in patients with schizophrenia. Neurite formation is identified as a crucial stage in development, and it is proposed that a defect in neurite formation originating from abnormally encoded proteins by these new genes could be at least an in vitro marker that ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 168 publications
2
59
0
Order By: Relevance
“…Defective neuritogenesis is the most consistent neuroanatomical finding in post-mortem studies of schizophrenia (Black et al, 2004;Guidotti et al, 2000;Glantz and Lewis, 2000) and in functional studies using animal models Ozeki et al, 2003;Bellon, 2007). Recently, two studies using induced pluripotent stem cell techniques showed that neurons derived from fibroblasts of human schizophrenia patients had reduced neurite numbers and neuronal connectivity (Brennand et al, 2011;Chiang et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Defective neuritogenesis is the most consistent neuroanatomical finding in post-mortem studies of schizophrenia (Black et al, 2004;Guidotti et al, 2000;Glantz and Lewis, 2000) and in functional studies using animal models Ozeki et al, 2003;Bellon, 2007). Recently, two studies using induced pluripotent stem cell techniques showed that neurons derived from fibroblasts of human schizophrenia patients had reduced neurite numbers and neuronal connectivity (Brennand et al, 2011;Chiang et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Several genes such as NRG-1, Akt1 and DISC have been shown to confer susceptibility for SCZ and proteins encoded by these genes are implicated in neurite formation in cellular and animal models of neurodevelopment. 74 In addition, the synaptic proteins VAMP-2 and SNAP-25 have demonstrated expression changes in SCZ and BPD and are also involved in neurite elongation and sprouting. 75 Further expression studies of proteins involved in neurite formation in these diseases are required to strengthen a hypothesis such as this.…”
Section: Discussionmentioning
confidence: 99%
“…The examination of different haplotypes of Akt, the most important downstream target of PI3K revealed mostly positive results [168,[176][177][178], however, also weak positive [175] and negative data exist [82,179]. In the light of the recent replications, the evidence for Akt as a susceptibility gene for schizophrenia is encouraging and warrants further investigation [173,175].…”
Section: Linking Phosphatidylinositide 3-kinase (Pi3k) Pathway To Schmentioning
confidence: 95%
“…Downstream targets of PI3K are V-akt murine thymoma viral oncogene homologue (Akt), glycogen synthase kinase (GSK3Beta), Beta Catenin and CREB, which had all been involved in the pathophysiology of the disease based on protein, mRNA and enzyme activity changes [168,[170][171][172]. Increased apoptosis due to abnormalities in Akt signaling could contribute to the pathophysiology of schizophrenia [173][174][175]. The examination of different haplotypes of Akt, the most important downstream target of PI3K revealed mostly positive results [168,[176][177][178], however, also weak positive [175] and negative data exist [82,179].…”
Section: Linking Phosphatidylinositide 3-kinase (Pi3k) Pathway To Schmentioning
confidence: 99%